Novel low-delay video transmission scheme based on SR-SW-HARQ - QIN Xiao-fang; YANG Da-cheng; ZHANG Xin (Tongxin xuebao)
To implement low delay video transmission, a novel scheme based on hybrid automatic repeat request （HARQ） technique was proposed. For three different priority-data based on H.264data partition mode, a combined protocol of selective repeat automatic repeat request （ARQ） and stop-and-wait ARQ was adopted at the link layer and an adaptive HARQ retransmission scheme was adopted at the physical layer. Comparing with the traditional scheme based on single slice mode, the simulation results show that less transmission delay and better throughput performance are achieved with improved video reconstructed quality.